2000
DOI: 10.1590/s1516-35982000000600015
|View full text |Cite
|
Sign up to set email alerts
|

Estimação de parâmetros genéticos de características reprodutivas em suínos

Abstract: RESUMO -Com o objetivo de estimar os parâmetros genéticos e fenotípicos de características reprodutivas de suínos, foram utilizados dados de peso da leitegada ao nascimento (PLN), peso da leitegada ajustado para 21 dias (PL21), tamanho de leitegada ao nascimento (TLN), tamanho de leitegada ao desmame (TLD) e taxa de mortalidade (TM), de três raças de suínos, Duroc, Landrace e Large White. Variâncias e covariâncias genéticas e fenotípicas foram estimadas pelo Método da Máxima Verossimilhança Restrita (REML), us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…In contrast to the performance traits, direct additive genetic values for reproductive traits showed no definite trend, which agrees with Chen et al (2003b), Pires (1999) and Irgang et al (1997) who observed very little genetic progress in reproductive traits of pigs. The low degree of genetic progress for the reproductive traits can be explained mainly by two factors.…”
Section: Genetic Trends In Pigs 99supporting
confidence: 83%
See 1 more Smart Citation
“…In contrast to the performance traits, direct additive genetic values for reproductive traits showed no definite trend, which agrees with Chen et al (2003b), Pires (1999) and Irgang et al (1997) who observed very little genetic progress in reproductive traits of pigs. The low degree of genetic progress for the reproductive traits can be explained mainly by two factors.…”
Section: Genetic Trends In Pigs 99supporting
confidence: 83%
“…Chen et al (2002) studied the genetic tendency of age to 113.5 kg and backfat adjusted for 113.5 kg in Large White, Duroc, Hampshire and Landrace pigs, and obtained lower estimates of maternal genetic that ranged from 0.01 to 0.05; the genetic trends for this effect were not reported. Pires (1999) also reported low estimates for a trend of maternal effect on reproductive traits. According to this author, one factor that could explain low, null or negative estimates of genetic trends for maternal effects is the antagonism between the direct and maternal effects since, when selection is based only on direct additive genetic effects, maternal ability tends to decrease.…”
Section: Genetic Trends In Pigs 99mentioning
confidence: 99%
“…Os valores encontrados neste trabalho estão dentro da amplitude de 0,61 a 0,89 encontrada por Pires et al (2000). Kaufmann et al (2000), ao estudarem a relação entre tamanho da leitegada e peso do leitão ao nascimento e ao desmame, encontraram associação negativa entre as características e ressaltaram que a seleção para tamanho da leitegada poderia levar à tendência negativa do efeito genético materno sobre o peso individual ao nascimento e ao desmame.…”
Section: Resultsunclassified
“…Lately, several works have used the common litter environmental effect in the models for better estimation of variance components, including those of reproductive traits (Kaufmann et al, 2000;Zhang et al, 2000;Lukovic et al, 2003;Lukovic et al, 2004;Chimonyo et al, 2006). Thus, a model that deals with maternal genetic, common litter environmental and direct genetic effects should provide more precise genetic parameter estimates for reproductive traits in swine than a model that contains only direct genetic effect (Roehe and Kennedy, 1993;Pires, 1999;Cavalcante Neto, 2006;Torres Filho et al, 2005). The main objective of this study was to evaluate the importance of including the maternal genetic, common litter environmental and permanent environmental effects in the estimation model of variance components of the farrowing interval in swine.…”
Section: Introductionmentioning
confidence: 99%